2013
DOI: 10.1016/j.jval.2013.08.812
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Population Health: An International Perspective Based on EQ-5D

Abstract: Bayer (83%), Gilead (80%), and Boehringer-Ingelheim (80%). The average time to receive a CDR recommendation varied from 170 days to 248 days. The manufacturers with the fastest time to recommendation are GSK, Abbott, Roche, Boehringer-Ingelheim, and Watson. Time to reimbursement / formulary listings in all provinces ranged from 123 days to 593 days. ConClusions: This is the first analysis to describe the success rate of pharmaceutical manufacturers through the CDR. There appears to high variability in all the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
5
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(171 citation statements)
references
References 0 publications
12
146
5
8
Order By: Relevance
“…While adjustments were made for sample structure, some of these factors may have influenced the comparability of the results. In particular, some surveys in the dataset archive were older, and limited evidence suggests that population norms may or may not change over time, depending on the country [3]. Non-response may have introduced a potential bias towards underestimation of self-reported health problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While adjustments were made for sample structure, some of these factors may have influenced the comparability of the results. In particular, some surveys in the dataset archive were older, and limited evidence suggests that population norms may or may not change over time, depending on the country [3]. Non-response may have introduced a potential bias towards underestimation of self-reported health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Among this research were surveys conducted in various countries that measured the health-related quality of life of the general population [3]. These EQ-5D surveys have been informative in providing new data on population health characteristics, complementing the traditionally collected morbidity and mortality data.…”
Section: Introductionmentioning
confidence: 99%
“…In order to define age-and gender-specific population norms, for both production and self-care, we used the raw data of two -respectively "self-care" and "usual activities" -of the five domains of the EQ-5D as presented in Szende et al [25]. Rather than relying on the single utility index as defined by EQ-5D and consequently taking into consideration the change in utility brought about by the disease/treatment, we decided to focus solely on the reduced ability to perform daily activities.…”
Section: Discussionmentioning
confidence: 99%
“…Age-and gender-specific health benchmark are derived from Szende et al [25], reporting self-reported population norms for 24 countries, based on the EQ-5D 2 questionnaire [26]. Given this, the model assumes that every year of life lived "below the norm" determines Societal costs, in terms of both paid and unpaid reduced production and in terms of augmented need of informal care.…”
Section: Societal Cost Of Reduced Abilitymentioning
confidence: 99%
See 1 more Smart Citation